Fine structure of coupled optical modes in photonic molecules - RAKOVICH, YURY; BRADLEY, LOUISE (My University, 2004)
We report on the coherent coupling of whispering gallery modes (WGM) in a photonic molecule formed from two melamine-formaldehyde spherical microcavities with a thin shell of CdTe nanocrystals. Utilizing a microporous polymer structure to orient the photonic molecule, we have excited the photonic molecule both on and off axis. This controllable geometry has allowed the observation of an off-axis fine structure that consists of very sharp peaks resulting from the removal of the WGM degeneracy with respect to the azimuthal quantum number m. The mode splittings are in very good agreement with theory.
PUBLISHED
Keywords: Physics